Marketing Strategy for Bank BJB to Increase Fee Base Income Mobile - Harsa Bani Partapraja, Harry; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2016)
Technological development and information are unavoidable, its usefulness. Many companies the world attempts to change itself into power generators (powerhouse) global business through various investment radicals in e-business, e-commerce, and effort information technology (IT) other incredibly global. So there is a need clear managers, business and practitioner business to understand how to manage a functional organization that this important.